Pipeline embolization device versus coiling for the treatment of large and giant unruptured intracranial aneurysms: a cost-effectiveness analysis - Wali, Arvin R.; Park, Charlie C.; Santiago-Dieppa, David R.; Vaida, Florin; Murphy, James D.; Khalessi, Alexander A. (Neurosurgical focus, 2017)
OBJECTIVE Rupture of large or giant intracranial aneurysms leads to significant morbidity, mortality, and health care costs. Both coiling and the Pipeline embolization device (PED) have been shown to be safe and clinically effective for the treatment of unruptured large and giant intracranial aneurysms; however, the relative cost-to-outcome ratio is unknown. The authors present the first cost-effectiveness analysis to compare the economic impact of the PED compared with coiling or no treatment for the endovascular management of large or giant intracranial aneurysms. METHODS A Markov model was constructed to simulate a 60-year-old woman with a large or giant intracranial aneurysm considering a PED, endovascular coiling, or no treatment in terms of neurological outcome, angiographic outcome, retreatment rates, procedural and rehabilitation costs, and rupture rates. Transition probabilities were derived from prior literature reporting outcomes and costs of PED, coiling, and no treatment for the management of aneurysms. Cost-effectiveness was defined, with the incremental cost-effectiveness ratios (ICERs) defined as difference in costs divided by the difference in quality-adjusted life years (QALYs). The ICERs < $50,000/QALY gained were considered cost-effective. To study parameter uncertainty, 1-way, 2-way, and probabilistic sensitivity analyses were performed. RESULTS The base-case model demonstrated lifetime QALYs of 12.72 for patients in the PED cohort, 12.89 for the endovascular coiling cohort, and 9.7 for patients in the no-treatment cohort. Lifetime rehabilitation and treatment costs were $59,837.52 for PED; $79,025.42 for endovascular coiling; and $193,531.29 in the no-treatment cohort. Patients who did not undergo elective treatment were subject to increased rates of aneurysm rupture and high treatment and rehabilitation costs. One-way sensitivity analysis demonstrated that the model was most sensitive to assumptions about the costs and mortality risks for PED and coiling. Probabilistic sampling demonstrated that PED was the cost-effective strategy in 58.4% of iterations, coiling was the cost-effective strategy in 41.4% of iterations, and the no-treatment option was the cost-effective strategy in only 0.2% of iterations. CONCLUSIONS The authors' cost-effective model demonstrated that elective endovascular techniques such as PED and endovascular coiling are cost-effective strategies for improving health outcomes and lifetime quality of life measures in patients with large or giant unruptured intracranial aneurysm.